Importance Ethnobotanique Et Des Menaces Sur Le Délice Du Boboye, Neocarya Macrophylla (Sabine) Prance, (Chrysobalanaceae) Dans La Vallée Fossile Du Dallol Bosso (Niger) - Kolafane, Aboubacar; Soumana, Douma; Moustapha, Adamou Mahaman; Abdoulaye, Hama Insa; Dolores, Agundez; Ramatou, Sidikou Djermakoye Seyni (European Scientific Journal, ESJ, 2018)
The present study conducted in the Dallol Bosso fossil valley aims to know the local perception of the level of threat on the Neocarya macrophylla species in order to provide indicators of sustainable management of the natural stand. To do this, surveys were conducted in two agro-ecological zones.The collection of information was carried out through a simple questionnaire based on the woody stand, the sources of supply and the part of the plant taken from the woody food species, as well as the threats they suffer and their causes. It appears that the most dominant species is Neocarya macrophylla ; a multipurpose species among others, used for food, medicine and wood.The survey also reveals the presence of twenty four (24) ligneous foods species among which eighteen (18) are common to both zones. Analyses showed, the excessive cutting of the wood and the unfavorable climatic conditions as the main factors resulting on potential threat of these species. At the same time, threats on Neocarya macrophylla, a characteristic species of Dallol Bosso valley were identified on the field.